Prevalence of Various Kennedy’s Classes in Partially Edentulous Patients Visiting in Prosthodontics Department of Isra Dental College Hyderabad - Farzana Memon, Saiwa Memon (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: To determine the prevalence of various missing teeth pattern among the partially edentulous patients who are undergoing treatment for the replacement of missing teeth. Methods: This descriptive study was conducted in the department of Prosthodontics, Isra Dental College Hyderabad, from January 2012 to March 2016. A total of 3603 patients age ranging from a minimum of 15 years to 75 years (1890 Males and 1713 females) were involved in the study. Detailed clinical examination of the patients were done and recorded in proforma. Data were analyzed using Statistics SPSS 21 version. Results: The results showed the patients with Kennedy’s Class III were found to be the most prevalent type among all the patients (73.8%). The most common modification in all patients was Class III modification I (19.8%). It was also found that Kennedy’s Class III were more commonly found in the age group of 40-49 years with 51.2% in the maxillary arch and 48.8% in the mandibular arch. Conclusion: In the conclusion, the partially edentulous condition exists common prevalence in the maxillary arch as compared with the mandibular arch. Kennedy’s Class III remains the most common classification.